Reduction and Morphological Transformation of Synthetic Nanophase Iron Oxide Minerals by Hyperthermophilic Archaea - Kashyap, Srishti; Sklute, Elizabeth C.; Dyar, M. Darby; Holden, James F. (Frontiers in Microbiology, 2018)
Fe(III) (oxyhydr)oxides are electron acceptors for some hyperthermophilic archaea in mildly-reducing geothermal environments. However, the kinds of iron oxides that can be used, growth rates, extent of iron reduction, and the morphological changes that occur to minerals are poorly understood. The hyperthermophilic iron-reducing crenarchaea Pyrodictium delaneyi and Pyrobaculum islandicum were grown separately on six different synthetic nanophase Fe(III) (oxyhydr)oxides. For both organisms, growth on ferrihydrite produced the highest growth rates and the largest amounts of Fe(II), although P. delaneyi produced four times more Fe(II) (25 mM) than P. islandicum (6 mM). Both organisms grew on lepidocrocite and akaganéite and produced 2-3 mM Fe(II). Modest growth occurred for both organisms on goethite, hematite, and maghemite where ≤ 1 mM Fe(II) was produced. The diameters of the spherical mineral end-products following P. delaneyi growth increased by 30 nm for ferrihydrite and 50-150 nm for lepidocrocite relative to heated abiotic controls. For akaganéite, spherical particle sizes were the same for P. delaneyi-reacted samples and heated abiotic controls, but the spherical particles were more numerous in the P. delaneyi samples. For P. islandicum, there was no increase in grain size for the mineral end-products following growth on ferrihydrite, lepidocrocite, or akaganéite relative to the heated abiotic controls. High-resolution transmission electron microscopy (HRTEM) of lattice fringes and selected-area electron diffraction (SAED) of the minerals produced by both organisms when grown on ferrihydrite showed that magnetite and/or possibly maghemite were the end-products while the heated abiotic controls only contained ferrihydrite. These results expand the current view of bioavailable Fe(III) (oxyhydr)oxides for reduction by hyperthermophilic archaea when presented as synthetic nanophase minerals. They show that growth and reduction rates are inversely correlated with the iron (oxyhydr)oxide crystallinity and that iron (oxyhydr)oxide mineral transformation takes different forms for these two organisms.